2023
DOI: 10.1186/s42523-023-00248-6
|View full text |Cite
|
Sign up to set email alerts
|

A phylogenomic and comparative genomic analysis of Commensalibacter, a versatile insect symbiont

Abstract: Background To understand mechanisms of adaptation and plasticity of pollinators and other insects a better understanding of diversity and function of their key symbionts is required. Commensalibacter is a genus of acetic acid bacterial symbionts in the gut of honey bees and other insect species, yet little information is available on the diversity and function of Commensalibacter bacteria. In the present study, whole-genome sequences of 12 Commensalibacter isolates from bumble bees, butterflies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 121 publications
0
9
0
Order By: Relevance
“…The presence of a correlation between the two samples indicated that just Nepenthes gracilis exhibits insectivorous behaviour, hence implying the potential presence of insect-related chemicals in its fluid. However, it is important to note that the statement presented here is just our hypothesis [3, 8, 14, 16].…”
Section: Results and Disscussionmentioning
confidence: 82%
See 2 more Smart Citations
“…The presence of a correlation between the two samples indicated that just Nepenthes gracilis exhibits insectivorous behaviour, hence implying the potential presence of insect-related chemicals in its fluid. However, it is important to note that the statement presented here is just our hypothesis [3, 8, 14, 16].…”
Section: Results and Disscussionmentioning
confidence: 82%
“…An analysis of the completeness of kegg metabolic pathways revealed a species-specific occurrence and degree of completeness of various metabolic pathways (). The results obtained demonstrated that Commensalibacter species had similar genetic potential in relation to carbohydrate metabolism but showed significant differences in their amino acid metabolism [8]. When compared to other species of the genus Commensalibacter , strain TBRC 10068 T contains the genome that encodes a pathway for histidine degradation to glutamate (M00045) but lacked the genomes for dissimilatory nitrate reduction (M00530) and molybdenum cofactor biosynthesis (M00880).…”
Section: Results and Disscussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed species descriptions are not part of the scope of most non-taxonomic journals, and therefore the possibility of publishing species descriptions in supplementary material of non-taxonomic journals would have opened the field of taxonomy to a broader microbiology audience. Below we provide descriptions of three novel Commensalibacter species published earlier as part of supplementary information of a paper in a journal targeting an audience of animal microbiome researchers [1] for the sole purpose of allowing the validation of their names. All taxonomic analyses and methods used to delineate the three novel species were presented earlier [1].…”
Section: Dear Editormentioning
confidence: 99%
“…Below we provide descriptions of three novel Commensalibacter species published earlier as part of supplementary information of a paper in a journal targeting an audience of animal microbiome researchers [1] for the sole purpose of allowing the validation of their names. All taxonomic analyses and methods used to delineate the three novel species were presented earlier [1].…”
Section: Dear Editormentioning
confidence: 99%